Management of Inedible Airway Foreign Bodies in Pediatric Rigid Bronchoscopy: Experience From a National Children's Regional Medical Center in China - Xu, Bin; Wu, Lei; Bi, Jing; Liu, Jia; Chen, Cao; Lin, Lexi; Chen, Chao; Qiu, Fei; Shang, Shiqiang (Frontiers in Pediatrics, 2022)
Abstract The aim of this study is to analyze the characteristics of inedible airway foreign bodies in pediatric rigid bronchoscopy to facilitate the improvement of management and technology. This retrospective analytical study was performed from January 2017 to June 2020. All admissions of pediatric patients (age＜18 years) with foreign-body aspiration diagnosis codes ([ICD]-10:T17 300, T17 400, T17 500 and T17 900) and procedure codes (33.7801) were extracted. Age, sex, preoperative history and imaging data, surgical records, length of hospital stay, reoperations and postoperative complications were included. Data were analyzed with SPSS 20. A total of 1237 patients were hospitalized and underwent rigid bronchoscopy. Forty-five (3.6%) patients with inedible foreign bodies in the airway were confirmed. There were no significant differences in sex, time of onset and length of hospital stay between the inedible and edible foreign body groups, except for age and a definite history of foreign body aspiration (P=0.000). Coughing, wheezing and fever were the common clinical symptoms in all patients. The following were the common locations of inedible foreign bodies: right bronchus (22/45), left bronchus (18/45), trachea (3/45) and larynx (2/45). The most frequent inedible foreign bodies were parts of a pen (15/45), a light-emitting diode (7/45) and plastic parts of toys (6/45). Vocal cord injury and a laryngeal web were observed in one case each. Conclusion: Rigid bronchoscopy is the method of choice for the removal of inedible foreign bodies. Adequate preoperative assessment to rely on CT scans, skillful operation techniques to avoid damaging and active management of postoperative complications are important for the success of the procedure.